2012
DOI: 10.1021/ja2116712
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Deubiquitinases Enabled by Chemical Synthesis of Proteins

Abstract: Ubiquitination/ubiquitylation is involved in a wide range of cellular processes in eukaryotes, such as protein degradation and DNA repair. Ubiquitination is a reversible post-translational modification, with the removal of the ubiquitin (Ub) protein being catalyzed by a family of enzymes known as deubiquitinases (DUBs). Approximately 100 DUBs are encoded in the human genome and are involved in a variety of regulatory processes, such as cell-cycle progression, tissue development, and differentiation. DUBs were,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 57 publications
3
43
0
2
Order By: Relevance
“…Earlier studies on the enzyme kinetics of UCH-L1, -L3 and -L5 N240 have established that both UCHs bind to ubiquitin with sub μM K M values161718193536. While UCH-L1 exhibits higher binding affinity for ubiquitin compared to that of UCH-L3, its hydrolysis turnover rate ( k cat ) is about two orders of magnitude slower than that of UCH-L3.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies on the enzyme kinetics of UCH-L1, -L3 and -L5 N240 have established that both UCHs bind to ubiquitin with sub μM K M values161718193536. While UCH-L1 exhibits higher binding affinity for ubiquitin compared to that of UCH-L3, its hydrolysis turnover rate ( k cat ) is about two orders of magnitude slower than that of UCH-L3.…”
Section: Resultsmentioning
confidence: 99%
“…Pimozide (an anti-psychotic drug) was identified as inhibitors of USP1, and auranofin (a rheumatoid arthritis drug) is a proteasome-associated DUB inhibitor (Chen et al, 2011; Liu et al, 2014). Benefiting from high-throughput screening studies, LS1 has been identified as a UCHL3 inhibitor and PR-619 has been characterized as a general DUB enzyme inhibitor (Edelmann, Nicholson, & Kessler, 2011; Ohayon, Spasser, Aharoni, & Brik, 2012). Interestingly, the mitochondria-localized DUB USP30 was found to be inhibited by a diterpenoid derivative 15-oxospiramilactone (S3), leading to the increased Mfn1/2 proteins which promote mitochondrial fusion (Yue et al, 2014).…”
Section: Dubs Targeting Therapeuticsmentioning
confidence: 99%
“…Pimozide (an anti-psychotic drug) was identified as inhibitors of USP1, and auranofin (a rheumatoid arthritis drug) is a proteasome-associated DUB inhibitor [154, 155]. Benefiting from high-throughput screening studies, LS1 as an UCHL3 inhibitor and PR-619 as a general DUB enzyme inhibitor [156, 157]. Interestingly, the mitochondria-localized DUB USP30 was found to be inhibited by a diterpenoid derivative 15-oxospiramilactone (S3), leading to the increased Mfn1/2 proteins which promote mitochondrial fusion [158].…”
Section: Dubs Involved In Diseases and Dubs Targeting Therapeuticsmentioning
confidence: 99%